2016
DOI: 10.1371/journal.pone.0150776
|View full text |Cite
|
Sign up to set email alerts
|

Viruses as Sole Causative Agents of Severe Acute Respiratory Tract Infections in Children

Abstract: BackgroundRespiratory syncytial virus (RSV) and influenza A viruses are known to cause severe acute respiratory tract infections (SARIs) in children. For other viruses like human rhinoviruses (HRVs) this is less well established. Viral or bacterial co-infections are often considered essential for severe manifestations of these virus infections.ObjectiveThe study aims at identifying viruses that may cause SARI in children in the absence of viral and bacterial co-infections, at identifying disease characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
3
26
2
Order By: Relevance
“…In addition, several factors may account for this disparity, including true differences in the overall burden or differences in study populations or methodologies [18,[23][24][25]. Moreover, infection rates vary with geographical location and season [22,26,27]. Finally, the specific viruses included in our screening decisions may account for the higher positive rates in our study.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, several factors may account for this disparity, including true differences in the overall burden or differences in study populations or methodologies [18,[23][24][25]. Moreover, infection rates vary with geographical location and season [22,26,27]. Finally, the specific viruses included in our screening decisions may account for the higher positive rates in our study.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies showed conflicting results on the impacts of viral infections on clinical outcomes in patients with SARI [9,13,14,19,22,23]. Differences in patients' numbers, enrollment criteria, and methodologies could explain these results.…”
Section: Discussionmentioning
confidence: 97%
“…In this scenario, superinfection exclusion mechanisms preventing a secondary infection with the same or a closely related virus should be envisaged (Folimonova, 2012). Although mixed infections have been widely assessed in ARTIs (Moesker et al, 2016;Seo et al, 2014;Turner et al, 2013), there is still no clear relationship with prolonged virus shedding, asymptomatic virus persistence, and disease severity. However, there is evidence that genome quantification could clarify the role of each virus in mixed infections (Franz et al, 2010;Martin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%